184k views
3 votes
PLEASE HELP ASAP!!! ):

PLEASE HELP ASAP!!! ):-example-1
User Mgamba
by
5.1k points

1 Answer

7 votes

9514 1404 393

Answer:

see attached

Explanation:

This is made slightly more difficult by the fact that the given polynomials are not in order of decreasing powers of x. So, you need to be careful what you're adding, to make sure the terms are "like".

__

Add: (-2x² +3x +4) +(x² -4x -5) = (-2+1)x² +(3-4)x +(4-5) = -x² -x -1

Opp: -(3x² -x +1) = 3x² +x -1

Sub: (x² +3x -4) -(-2x² +4x -3) = (1-(-2))x² +(3-4)x +(-4-(-3)) = 3x² -x -1

PLEASE HELP ASAP!!! ):-example-1
User Alexandr Panteleev
by
5.1k points